2015
DOI: 10.4251/wjgo.v7.i10.184
|View full text |Cite
|
Sign up to set email alerts
|

Role of retinoids in the prevention and treatment of colorectal cancer

Abstract: Vitamin A and its derivatives, retinoids, have been widely studied for their use as cancer chemotherapeutic agents. With respect to colorectal cancer (CRC), several critical mutations dysregulate pathways implicated in progression and metastasis, resulting in aberrant Wnt/β-catenin signaling, gain-of-function mutations in K-ras and phosphatidylinositol-3-kinase/Akt, cyclooxygenase-2 over-expression, reduction of peroxisome proliferator-activated receptor γ activation, and loss of p53 function. Dysregulation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 180 publications
2
32
0
Order By: Relevance
“…The reduced migration and invasion of cancer cell lines induced by retinoids correlate in animal models with decreased tumor growth and metastases (Tabata et al, 2009;Zhao et al, 2009;Benelli et al, 2010;Applegate and Lane, 2015;Waters et al, 2015;Williams et al, 2018). These effects together with other beneficial actions have motivated the use of retinoids for the treatment of several malignancies, including acute promyelocytic leukemia (Cicconi et al, 2018;Lengfelder et al, 2018), head and neck squamous cell carcinoma (Bhatia et al, 2017), and neuroblastoma (Cheung, 2015).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The reduced migration and invasion of cancer cell lines induced by retinoids correlate in animal models with decreased tumor growth and metastases (Tabata et al, 2009;Zhao et al, 2009;Benelli et al, 2010;Applegate and Lane, 2015;Waters et al, 2015;Williams et al, 2018). These effects together with other beneficial actions have motivated the use of retinoids for the treatment of several malignancies, including acute promyelocytic leukemia (Cicconi et al, 2018;Lengfelder et al, 2018), head and neck squamous cell carcinoma (Bhatia et al, 2017), and neuroblastoma (Cheung, 2015).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Accumulative researches indicated that retinoids were associated with the prevention and amelioration of numerous chronic diseases and cancers [2932]. Retinoids are currently used as chemotherapies against cancers of epithelial origin [33].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we reported that AtRA inhibited the NO production in proinflammatory cytokines stimulated peripheral blood mononuclear cells (PBMC) and monocytes from IBD and Alzheimer disease patients [11, 39]. Furthermore, retinoids are known to affect signaling pathways frequently altered which result in the development and progression of CRC [32]. In this sense, understanding the pathway involved in cancer-related inflammation and targeting transcription factors such as NF- κ B has attracted our attention.…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer, an aggressive malignancy causes substantial morbidity and mortality (1,2). The current treatment for patients with colon cancer relies on chemotherapy, despite its severe side-effects.…”
Section: Introductionmentioning
confidence: 99%